2008
DOI: 10.1007/s00020-008-1604-7
|View full text |Cite
|
Sign up to set email alerts
|

Convolution-Dominated Operators on Discrete Groups

Abstract: Consider a discrete group G and a bounded self-adjoint convolu-tion operator T on l 2 (G); let σ(T) be the spectrum of T. The spectral theorem gives a unitary isomorphism U between l 2 (G) and a direct sum n L 2 (∆n, ν), where ∆n ⊂ σ(T), and ν is a regular Borel measure supported on σ(T). Through this isomorphism T corresponds to multiplication by the identity function on each summand. We prove that a nonzero function f ∈ l 2 (G) and its transform Uf cannot be simultaneously concentrated on sets V ⊂ G, W ⊂ σ(T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
63
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 27 publications
(63 citation statements)
references
References 26 publications
0
63
0
Order By: Relevance
“…The proof is completely similar to that of Theorem 1.7 using the fact, proved in [9] (see also [24] for a weaker statement) that C ω (G) is a spectral involutive algebra for all admissible weight.…”
Section: Application To the Class Of Convolution-dominated Operatorsmentioning
confidence: 77%
“…The proof is completely similar to that of Theorem 1.7 using the fact, proved in [9] (see also [24] for a weaker statement) that C ω (G) is a spectral involutive algebra for all admissible weight.…”
Section: Application To the Class Of Convolution-dominated Operatorsmentioning
confidence: 77%
“…Furthermore, by using the same technical lemma of Bickel and Lindner [2], we are able to show (by a quite short proof) that, for a group with subexponential growth, the Wiener algebra of the group is a spectral invariant dense subalgebra of the uniform Roe algebra (Theorem 4.9). This result can be viewed as a generalization of a recent result by Fendler, Gröchenig and Leinert [9] which shows that the Wiener algebra of the group is a spectral invariant dense subalgebra of the uniform Roe algebra for groups with polynomial growth.…”
Section: Introductionmentioning
confidence: 89%
“…Hence W is a dense Banach subalgebra of C * u (G) via left convolutions on 2 (G). In [9], Fendler, Gröchenig, Leinert showed that if G is amenable and rigidly symmetric, then W is a spectral invariant subalgebra of B( 2 (G)). The main examples of amenable and rigidly symmetric groups are groups with polynomial growth.…”
Section: Theorem 45 Assume That G Has Polynomial H-growth With Respementioning
confidence: 99%
“…Proof. Like in [7] we define a representation R of L, but this time on L 2 (G) = i∈H L 2 (U). The image of R will turn out to be CD H .…”
Section: Spectrality Of CD ∞ and Cd Hmentioning
confidence: 99%
“…Since H is amenable and l ∞ (H, B(L 2 (U))) is a C * algebra, by Leptin [20] the Mregular representation is a maximal representation of B. It is weakly equivalent to R. To see this one slightly modifies the proof of [7,Prop 3]. Since R happens on L 2 (G) = l 2 (H, L 2 (U)) and λ M happens on l 2 (H, L 2 (G)) = l 2 (H × H, L 2 (U)), we work on this last space, which we denote H for short.…”
Section: Spectrality Of CD ∞ and Cd Hmentioning
confidence: 99%